Texts for the Historiography Linguistic of Puerto Rico: The Work of Zacarías Vall Espinosa (1886 and 1887) - García Aranda, Ma Ángeles (Káñina, 2020)
Between 1886 and 1886 Zacarías Vall Espinosa, an English teacher of Spanish origin, published in Ponce (Puerto Rico) two grammars to teach English to Puerto Rican youth. Although his texts are not very original, Vall Espinosa constitutes an interesting contribution to the history of the teaching of second languages and to the, still to be done, Linguistic Historiography of Puerto Rico.